Analysis of the Promoter of Emb5 from Zea mays Identifies a Region of 523 bp Responsible for Its Embryo-Specific Activity - Yang Li; Liping Yu; Qiushuang Wang; Xiangyu Zhao; Xinzheng Li; Baoxiu Qi (Plant Molecular Biology Reporter, 2021)
The maize Emb5 is an abscisic acid–responsive gene which is specifically expressed in the late embryo during seed maturity. To further dissect and identify the elements specific for its embryo expression pattern, we investigated the activity of the − 1653 bp upstream of the “full-length” promoter region of this gene in transgenic Arabidopsis plants. We first confirmed that the “full-length” promoter could indeed drive the expression of β-glucuronidase reporter gene ( GUS ) in the transgenic Arabidopsis seed embryo. Subsequently, DNA fragments of ~ 500 bp in length were generated after a series of progressive deletions from positions − 1653 bp to − 1 bp relative to the transcriptional initiation site. These fragments were fused with GUS and introduced into Arabidopsis. Measurement of the GUS activity in the immature seeds isolated from the transgenic plants revealed that the region between positions − 523 bp and − 1 bp, namely Pro Em-D, is absolutely required and sufficient for the temporal and embryo-specific expression of GUS with an activity comparable with the full-length Emb5 promoter in Arabidopsis. Therefore, our results clearly demonstrated that the 523 bp Pro Em-D can replace the − 1653 bp Emb5 promoter to drive embryo-specific expression in Arabidopsis seed. Because of its small size and strong embryo-specific activity, it could become the promoter of choice in metabolic pathway engineering to transfer multiple genes for the production of valuable pharmaceutical products in seeds, such as polyunsaturated fatty acids found in fish oils, or pro-vitamin A where at least three transgenes are required to assemble the entire metabolic pathways.